A clinical study on cognitive dysfunction in depressed patients - Karnik Kishore; Deepanjali Medhi (Industrial Psychiatry Journal)
Background: Major depression is a commonly occuring, seriously impairing, and often recurrent mental disorder. Depression and cognitive impairement have enormous implications for public health. Cognitive symptoms represent one of the core features of depression and have an impact on many functional outcomes. Different cognitive domains such as attention and concentration, psychomotor speed, executive functioning, and memory have been found to be implicated. Aim: This study aimed at assessing the cognitive domains affected and severity of cognitive dysfunction in first-episode patients of the unipolar depressive episode without psychosis and to assess the correlation of association of severity of cognitive deficit with severity of depression. Materials and Methods: A total of 40 patients with depression diagnosed according to International Classification of Diseases Research Diagnostic Criteria and 40 healthy controls were included. PGI Battery of Brain Dysfunction, Frontal Assessement Battery, and Hamilton Depression Rating scale (HAM–D) were adminstered, and analysis was done using Chi-square test, unpaired t-test, and Pearson’s correlation. Results: The study revealed significant differences in the dysfunction scores between the study and control populations. In the study group, more than 80% of patients had cognitive dysfunction and a positive correlation was found between dysfunction and HAM–D scores. Conclusion: Depression is associated with significant disturbance in cognitive functioning, and the cognitive dysfunction increases with an increase in the severity of depression.